2020
DOI: 10.1158/1541-7786.mcr-19-0564
|View full text |Cite
|
Sign up to set email alerts
|

RAIN Is a Novel Enhancer-Associated lncRNA That Controls RUNX2 Expression and Promotes Breast and Thyroid Cancer

Abstract: Enhancer (ENH)-associated long noncoding RNAs (lncRNA) are a peculiar class of RNAs produced by transcriptionally active ENHs, owning potential gene-regulatory function. Here, we characterized RAIN, a novel ENH-associated lncRNA. Analysis of RAIN expression in a retrospective cohort of human thyroid cancers showed that the expression of this lncRNA is restricted to cancer cells and strongly correlates with the expression of the cancer-promoting transcription factor RUNX2. We showed that RAIN, serving as a cisr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In the initial stage of lncRNA research, some scholars suggested that there is a difference in the expression of lncRNAs between tumor tissues and adjacent normal tissues. An increasing number of studies 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 have shown that lncRNAs may play an important biological role in the regulation of cancer development, as the biological function of lncRNAs in carcinomas is to promote cancer cell proliferation and invasion, suppress cancer cell proliferation and invasion, estimate the prognosis and efficacy, and act as potential biomarkers, as summarized in Table 1 .…”
Section: Biological Function Of Lncrnas In Carcinomasmentioning
confidence: 99%
“…In the initial stage of lncRNA research, some scholars suggested that there is a difference in the expression of lncRNAs between tumor tissues and adjacent normal tissues. An increasing number of studies 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 have shown that lncRNAs may play an important biological role in the regulation of cancer development, as the biological function of lncRNAs in carcinomas is to promote cancer cell proliferation and invasion, suppress cancer cell proliferation and invasion, estimate the prognosis and efficacy, and act as potential biomarkers, as summarized in Table 1 .…”
Section: Biological Function Of Lncrnas In Carcinomasmentioning
confidence: 99%
“…Non-coding RNAs are emerging as new key players in genomic function organization [76]. Micro RNAs (miRNAs) are short RNA molecules 18-25 nucleotides in length.…”
Section: Micro Rnasmentioning
confidence: 99%
“…WDR5 is a fundamental member of the histone H3K4 methyltransferase complexes ( Rossi , [ 46 ]). WDR5 promoted H3K4 trimethylation on active promoters and facilitated the recruitment of RNA-Pol-II for transcriptional activation of target genes.…”
Section: Interplay Between Lncrnas and Runx1mentioning
confidence: 99%
“…RAIN restrained the NELFe-induced inhibitory effects on RUNX2 expression. There was a significant upregulation of RUNX2 in NELFe-silenced MDA-MB-231 and TPC1 cancer cells ( Rossi , [ 46 ]).…”
Section: Interplay Between Lncrnas and Runx1mentioning
confidence: 99%